2017
DOI: 10.2337/db17-0306
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypoglycemia–Induced Fatal Cardiac Arrhythmias Are Augmented by Diabetes and Attenuated by Recurrent Hypoglycemia

Abstract: We previously demonstrated that insulin-mediated severe hypoglycemia induces lethal cardiac arrhythmias. However, whether chronic diabetes and insulin deficiency exacerbates, and whether recurrent antecedent hypoglycemia ameliorates, susceptibility to arrhythmias remains unknown. Thus, adult Sprague-Dawley rats were randomized into four groups: 1) nondiabetic (NONDIAB), 2) streptozotocin-induced insulin deficiency (STZ), 3) STZ with antecedent recurrent (3 days) hypoglycemia (∼40–45 mg/dL, 90 min) (STZ+RH), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…Hence, hypoglycemia was preceded by a relatively small decline in plasma glucose (PG). It has also been suggested that diabetes may aggravate the risk of cardiac rhythm abnormalities ( 11 , 15 ); however, in the only study comparing the electrophysiological response to hypoglycemia in patients with type 2 diabetes with the response in controls without diabetes, only a fraction of the patients with type 2 diabetes were insulin-treated ( 11 ). Consequently, it is uncertain whether the results from this study translate into a risk population of insulin-treated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, hypoglycemia was preceded by a relatively small decline in plasma glucose (PG). It has also been suggested that diabetes may aggravate the risk of cardiac rhythm abnormalities ( 11 , 15 ); however, in the only study comparing the electrophysiological response to hypoglycemia in patients with type 2 diabetes with the response in controls without diabetes, only a fraction of the patients with type 2 diabetes were insulin-treated ( 11 ). Consequently, it is uncertain whether the results from this study translate into a risk population of insulin-treated patients.…”
Section: Introductionmentioning
confidence: 99%
“…20 In a diabetic rodent model with streptozotocintreated diabetic rats, insulin-deficiency more than doubled the risk of third-degree AV block and death during severe hypoglycaemia compared with nondiabetic rats. 21 However, exposure of QTc, corrected QT interval.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…streptozotocin-treated rats to antecedent moderate hypoglycaemia the days before being exposed to hypoglycaemia resulted in reduced sympatoadrenergic response during severe hypoglycaemia and a significant reduction in third-degree AV block and mortality compared with nondiabetic rats. 21 Hence, while diabetes might increase the risk of fatal cardiac arrhythmias during severe hypoglycaemia, antecedent hypoglycaemia blunts the sympatoadrenergic response to hypoglycaemia, which might serve as a mediator of cardiac arrhythmias during severe hypoglycaemia. 21 Although the abovementioned findings point towards a central role for catecholamines and the sympathetic nervous system in cardiac arrhythmias during severe hypoglycaemia, they have recently been contradicted by a study from the same group.…”
Section: Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that the risk of AF in individuals with insulin-deficient (type 1 and advanced type 2) diabetes increased with worsening glycemic control and periods of hypoglycemia ( 11 13 ). Similarly, severe hypoglycemia-induced fatal cardiac arrhythmias were enhanced in diabetic rats with insulin deficiency ( 14 ). Recently, we demonstrated that long term high-fat diet-induced insulin resistance enhanced the vulnerability of AF induction in a rodent model ( 15 ).…”
Section: Introductionmentioning
confidence: 99%